PENGARUH KEKERAPAN MEMBACA SURAT KABAR TERHADAP KEMAMPUAN MEMAHAMI WACANA - Golda Mair (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
ABSTRACTThis  study aims  to  determine the  frequency  of reading the  newspaper, the  ability to understand the discourse and influence the frequency of reading a newspaper on the ability to understand the discourse. The population in this study were students of class X SMA Methodist 8 Medan  Year  2009/2010  Learning  totaling  110  people.  Samples  were  taken  30  people.The method used in this research is descriptive method. Data collection tool used questionnaires and tests. The questionnaire used to collect the data frequency of reading newspapers and essaytests used to collect data is the ability to understand the discourse.Once the data is collected and analyzed the results of the study showed that the statesIncidence  Reading  Newspaper  Methodist  High  School  Class  X  8  Medan  Year  2009/2010Learning is  at sufficient levels to an  average value  of 65, Ability Discourse UnderstandingMethodist High  School Class  X 8 field of Learning 2009/2010 are  at a  high level with an average  value  of  68.5,  and  the  Effect Frequency  Reading  the  news letter to  the ability  ofDiscourse Understanding Class X 8 Terrain Methodist high School Year 2009/2010 are learningat a very strong level is 0.857.To test the hypothesis, used product moment correlation formula is 0.857 Furthermore,in consultation with the db table r N-2 (30-2) = 28, r = db table for 28 is 0.374. Thus rh  rt(0.857> 0.374), determination index obtained from the calculation is 73.44%. So the influence ofthe frequency of reading the newspaper with the ability to understand the discourse of class X SMA Methodist 8 Medan Year 2009/2010 Study of 73.44% means that the hypothesis (Ha) readsthe frequency of reading newspapers significantly affect the ability to understand the discourse of  class  X  SMA  Methodist  8  Medan  Year  2009/2010  Learning  acceptable.Keywords : frequency of reading, newspaper, understand discourse